Dampak sektor industri pengolahan terhadap perekonomian Provinsi Jambi (Pendekatan Input Output) - Suroto Suroto; Muhammad Syurya Hidayat; Muhammad Safri (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
This study aims to analyze: 1) the role and relevance of the processing industry sector in the economic structure of Jambi Province; 2) the impact of the processing industry on output, labor absorption and income in Jambi Province; 3) the processing sub-sector which is the leading sector in Jambi Province. The main data used is the Jambi Province Input-Output Table in 2007. Data analysis included linkage and dissemination analysis, multiplier analysis and standardization and analysis of the determination of priority sectors through ranking each sector. The results of the study found: 1) the processing industry sector in Jambi Province had an important role to play in the structure of demand and supply, public consumption, investment, exports and imports, gross value added and sectoral output structures. The manufacturing industry sector also has strong links to other sectors; 2) based on the analysis of output multiplier, income multiplier, labor multiplier, in type I the processing industry is ranked second, while in type II the processing industry is ranked third; 3) the processing sub-sector which is the leading sector in Jambi Province is the other goods industry sub-sector, the textile, leather and footwear sub-sector and the beverage industry subsector.